The Effectiveness of Mindful Sport Performance Enhancement (MSPE) and Mental Imagery (MI) on Improving Basketball Free Throws - Saleh Moazam; Rasoul Hemayat Talab; Hassan Gharayagh Zandi; Mohammad khazaei (University of Tehran, 2022)
AbstractThe present study was conducted to compare the effectiveness of two different methods to enhance free throw shooting among young basketball players. One method is based on mindfulness(MSPE) and the other is based on mental imagery(MI). This is a semi-experimental study and in terms of data collection, the design of the study is experimental with pre-test, post-test and a control group. Statistical population consisted of young basketball players in Tehran from whom 60 players were selected through convenience sampling and put into the following three groups: mindfulness group, mental imagery group and control group. Statistical analyses were presented in two sections: descriptive statistics and inferential statistics. Descriptive statistics included participants' characteristics, distribution of data and the variables' mean and standard deviation. Shapiro-Wilk test was also used to determine whether the data were naturally occurring. Then, the data were analyzed through inferential statistics using paired-samples T-Test, ANOVA, Leven's Test, Games-Howell Test and Bonferroni post hoc Test to test the hypotheses. Significance level of the study was set at 0.05. The results obtained from the pre-test and post-test of both mindfulness and mental imagery groups showed the participants' performance was significant with mean differences of 4.15 and -2.55 respectively. Also, the final findings of the study indicated that treatment in mindfulness group was more effective than that of mental imagery group, in improving free throw shooting (P=0.2).Key words: basketball, Free throw, Mindfulness, Mental imagery, Sport performance